The relationship between trade openness and FDI inflows: Evidence-based insights from ASEAN region - Abdulrahman A. Albahouth; Muhammad Tahir (Economies, 2024)
This research paper focuses on figuring out the impact of trade openness on FDI inflows, which has received relatively less attention in the literature, specifically in the context of ASEAN economies. The ASEAN region, which is relatively more open in terms of both trade openness as well as FDI inflows, is chosen as a sample. Annual data are gathered from 'World Development Indicators (WDI)' and 'World Governance Indicators (WGI)'. Reported results and findings are based on 'Fixed Effect (FE) Modeling', and the 'Generalized Least Square (GLS)' is utilized for the robustness check. The results indicated that trade openness matters significantly for attracting FDI inflows. Similarly, institutional quality has also exerted a positive and significant influence on the inflows of FDI. The disaggregated analysis shows that five aspects of institutional quality, such as rule of law, regulatory quality, control of corruption, voice and accountability, and political instability and absence of violence, have positively and significantly impacted the FDI inflows in the case of selected ASEAN economies. The results demonstrated that exchange rate depreciation is harmful for the inflows of FDI. Moreover, FDI inflows responded positively to market size. Furthermore, the results showed that the impact of natural resources and inflation on FDI inflows is insignificant statistically. The present study suggests that the ASEAN policymakers manage their exchange rate effectively, improve the quality of institutions, and adopt vigorous trade liberalization policies to attract more FDI inflows.
Keywords: 330; FDI; ASEAN; institutional quality; panel data; trade openness